Reformasi Sistem Pelayanan Publik Melalui Mobile Jkn Di Bpjs Kesehatan Kota Padang - Dwi Finta, Dea; Syamsir, Syamsir; Putra Adriyan, Dendi; Muhammad, Fadel; Febrilia, Irma; Cahyani , Widya (CV RIFAINSTITUT, 2022)
Bureaucratic reform is a fundamental change in the paradigm and governance of Indonesian government. On the basis of the desire for bureaucratic reform, the government seeks to improve the bureaucratic process. However, especially with regard to BPJS Health, it is still not running as expected, such as BPJS Health services which are sometimes often crowded, queued, and convoluted. With reform, there is a great need for digitization through the JKN mobile application. This method and writing uses a qualitative approach. Qualitative writing uses descriptive data, namely in the form of written or spoken words from people and observable behavior. This research utilizes open interviews to examine and understand attitudes, views, feelings and behavior of individuals or groups of people. Padang City Health BPJS services through Mobile JKN are getting better. It looks like participants don't have to come and queue to go to the office, and through their cellphones, everything they want is in mobile JKN and at the same time within their grasp, but it's also undeniable that as long as using the application there are still problems but they can still be controlled. So the presence of a digital-based service system reform makes it easier for the community